2019
DOI: 10.1097/inf.0000000000002208
|View full text |Cite
|
Sign up to set email alerts
|

Disease- and Treatment-related Morbidity in Adolescents With Perinatal HIV Infection in Asia

Abstract: Background: Perinatally HIV-infected adolescents (PHIVA) are exposed to a chronic systemic infection and long-term antiretroviral therapy (ART), leaving them susceptible to morbidities associated with inflammation, immunodeficiency, and drug toxicity. Methods: Data collected 2001-2016 from PHIVA aged 10-19 years within a regional Asian cohort were analysed using competing risk time-to-event and Poisson regression analyses to describe the nature and incidence of morbidity events and hospitalisations, and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The crude rate of hospitalization (6.6/100-person years) was higher than in HIV− adolescents in this study and higher than in HIV+ adolescents from other contexts (1.8 per 100-person years in a study that represented 6 countries in Asia). (10) Despite most adolescents having well controlled HIV disease, this rate is similar to the pre-ART rate reported in the US (6.5 per 100-person years) in 1994. (17) The high rate of hospitalization may partly be explained by higher exposure to infectious comorbidities such as TB and the fact that ART was started at a later age compared to those in the USA.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The crude rate of hospitalization (6.6/100-person years) was higher than in HIV− adolescents in this study and higher than in HIV+ adolescents from other contexts (1.8 per 100-person years in a study that represented 6 countries in Asia). (10) Despite most adolescents having well controlled HIV disease, this rate is similar to the pre-ART rate reported in the US (6.5 per 100-person years) in 1994. (17) The high rate of hospitalization may partly be explained by higher exposure to infectious comorbidities such as TB and the fact that ART was started at a later age compared to those in the USA.…”
Section: Discussionsupporting
confidence: 70%
“…A study of PHIV+ adolescents on ART from Asian countries reported a crude hospitalization rate of 2.2 per 100-person years. (10) There were more infectious related morbidities in early adolescence (10-14 years) with a trend toward non-infectious and treatment related morbidity in later adolescence (15-19 years). Inhospital mortality in Zimbabwean HIV+ adolescents was more than three times that of HIV− adolescents.…”
mentioning
confidence: 93%
“…Another study conducted in China found that patients with a baseline VL > 100,000 copies/mL were 3.2 times more likely to experience virologic failure (26), and a study on youth with HIV infection found that a low baseline VL was a predictor of viral suppression (AHR = 1.56) (27). Additionally, a high baseline VL can continue to damage the immune system and increase the possibility of opportunistic infections and AIDS-related mortality (28,29). A study on TB-HIV patients found that patients with higher baseline VL were more likely to experience virologic failure (AOR=1.5) (30).…”
Section: Last Art Regimenmentioning
confidence: 99%
“…Single system morbidity has been described in resource limited settings, mostly focusing on cardiac or chronic lung disease [12,13]. A recent study from Asia showed that infectious HIV-related morbidity was more common in younger adolescence (10 to 14 years of age) with a trend toward noninfectious and treatment-related morbidity in later adolescence, however, this study did not specifically explore chronic or multisystem morbidity [14].…”
Section: Introductionmentioning
confidence: 95%